Future of Islamic State: Not Merely Religion - Mushahid Ali (2016)
Despite globally purveying Wahhabism, Saudi Arabia is increasingly concerned that it could be identified with extremist groups like Islamic State. Saudi officials and pundits point to the kingdom’s efficient counterterrorism measures as well as gradual changes in the country. Ideological confrontation of IS philosophy alone is unlikely to eradicate the threat. Tackling the root causes of the appeal of jihadism will.